Influence of body condition on the population dynamics of Atlantic salmon with consideration of the potential impact of sea lice - Susdorf, R; Salama, N K G; Lusseau, D (Journal of fish diseases, 2018)
Atlantic salmon Salmo salar is an iconic species of high conservation and economic importance. At sea, individuals typically are subject to sea lice infestation, which can have detrimental effects on their host. Over recent decades, the body condition and marine survival in NE Atlantic stocks have generally decreased, reflected in fewer adults returning to rivers, which is partly attributable to sea lice. We developed a deterministic stage‐structured population model to assess condition‐mediated population dynamics resulting in changing fecundity, age at sexual maturation and marine survival rate. The model is parameterized using data from the North Esk system, north‐east Scotland. Both constant and density‐dependent juvenile survival rates are considered. We show that even small sea lice‐mediated changes in mean body condition of MSW can cause substantial population declines, whereas 1SW condition is less influential. Density dependence alleviates the condition‐mediated population effect. The resilience of the population to demographic perturbations declines as adult condition is reduced. Indirect demographic changes in salmonid life‐history traits (e.g., body condition) are often considered unimportant for population trajectory. The model shows that Atlantic salmon population dynamics can be highly responsive to sea lice‐mediated effects on adult body condition, thus highlighting the importance of non‐lethal parasitic long‐term effects.